Development of a bio-inkjet printed LAMP test kit for detecting human African trypanosomiasis. - Kyoko Hayashida; Peter Nambala; Nick Van Reet; Philippe Büscher; Naoko Kawai; Mable Mwale Mutengo; Janelisa Musaya; Boniface Namangala; Chihiro Sugimoto; Junya Yamagishi (Public Library of Science (PLoS), 2020)
Human African trypanosomiasis (HAT) is one of the neglected tropical diseases in sub-Saharan Africa. Early diagnosis and treatment prior to disease progression are crucial for the survival of HAT patients. We had previously established a loop-mediated isothermal amplification (LAMP) method for HAT diagnosis in which the reagents were dried for field-use purposes. In this study, we used a semi-automated process to produce the test tubes using a bio-inkjet printer to achieve an accurate production. The performance of the inkjet printer-produced dried LAMP test (CZC-LAMP) was found to be stable after storage for up to 180 days at 30 °C. The diagnostic accuracy of CZC-LAMP HAT was evaluated using DNA samples that were extracted from 116 Trypanosoma brucei gambiense patients and 66 T. b. rhodesiense patients. The sensitivity was 72% for T. b. gambiense (95%CI: 63%-80%) and 80% for T. b. rhodesiense (95%CI: 69%-89%). The specificity determined using DNA from 116 endemic control DNA samples was 95% (95%CI: 89%-98%). The performance of the CZC-LAMP HAT and CZC-LAMP rHAT were also evaluated using 14 crude blood lysate samples obtained from T. b. rhodesiense patients and endemic control samples collected from Rumphi District in Malawi. The sensitivity and specificity were both 100% (95%CI: 77%-100%). As the developed CZC-LAMP test does not require a cold chain or a sophisticated laboratory, it holds promise for use as a routine simple molecular tool for point-of-care HAT diagnosis in endemic areas.